Assessment Gamification with Fhoment Methodology: An Action Research Based Case Study - Ecar, Miguel; da Silva, João Pablo Silva (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
Gamification has been one of the most popular modern strategies in high education. It is used in different approaches, and several goals. Gamification can be used to stimulate learning, and obtain knowledge by side effect, while playing. Students assessment is a topic that that divides opinions. At the same time there must be an evaluation strategy, there is no a specific one that may be said completely fair. Several problems may impact in the student assessment score, with no directly relation to knowledge. In order to reach this problem, we propose Free Choice to Obtain Assessment Benefit (Fhoment) Methodology. Fhoment is a methodology that offers assessment benefits in exchange of currencies, obtained through assignments. We Applied Fhoment Methodology in 2 under graduation courses. Results shows good acceptance from students, better students involvement and significant impact on assessment results.